Pengembangan Media Pembelajaran IPAS berbasis Lectora Inspire untuk Meningkatkan Hasil Belajar Siswa Kelas IV SD Negeri Kebondowo 01 Kabupaten Semarang - Alvina Verda Ardani; Desi Wulandari (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2026)
This research is a Research and Development (R&D) development study with the ADDIE model which aims to develop, test the feasibility, and test the effectiveness of Lectora Inspire-based science learning media on the material